Peran Guru dalam Mengembangkan Kemampuan Membaca Permulaan pada Siswa Kelas 1 MI - Abdul Alim; Alfandi Alfandi; Saiful Hamdi (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aims to describe the role of teachers in developing the early reading skills of first-grade students at MI TGH. Muhammad Shadruddin NW Suralaga in 2026. The background of this study is based on the low and uneven distribution of students' early reading skills, characterized by difficulties in recognizing letters, reading syllables, and reading simple words and sentences. This study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation. The results showed that students' early reading skills varied, with the majority falling in the moderate and low categories. The teacher's role was very dominant in developing early reading skills, namely as a facilitator, motivator, guide, and evaluator. Teachers used the syllable method, phonics method, and repeated reading exercises, supported by media such as letter cards, word cards, and picture story books. Obstacles faced included differences in student abilities, low interest in reading, limited time, and lack of parental support. Teachers' efforts, such as individual guidance, motivation, and the use of simple learning media, have been shown to gradually improve students' reading skills. Therefore, it can be concluded that the teacher's role is crucial in successfully developing students' beginning reading skills.